THE EFFECT OF glycyrrhiza glabra AND DIOSPYROS KAKIFRUITS IN INHIBITING THE CHROMOSOMALABERRATIONS RESULTED FROM SODIUM SULFATETREATMENT IN HUMAN LYMPHOCYTE - Husain, Raheem; Shawket, Muayad; Galoob, Abd- Alameer (Iraqi Journal of Science, 2024)
To study the role of Glycyrrhiza glabra and Diospyros kaki fruits extracts, activecompounds were detected. The first extract contained glycoside, tannines, alkaloids,saponines, terpines, steroides, flavones and coumarins, while the second extractcontained phenolics and resins in addition to the compounds mentioned above withan exception of alkaloids and coumarins.The inhibition effect of the extracts on the chromosomal aberration resulted fromsodium sulfate as mutagenic agent in human lymphocyte cells (In vitro) was evaluated at concentrations of 10, 15, 25, 50, 100 mcg/ml. Results showedincreasing in inhibition of the extracts on chromosomal aberration with the increaseof the concentrations used and its interaction.